Continuous positive airway pressure therapy in non-sleepy patients with obstructive sleep apnea: results of a meta-analysis - Zhang, Dongmei; Luo, Jinmei; Qiao, Yixian; Xiao, Yi (Journal of Thoracic Disease, 2016)
Background: Although continuous positive airway pressure (CPAP) has become the first line of therapy for obstructive sleep apnea (OSA), it remains controversial whether non-sleepy patients could benefit from CPAP treatment. Methods: We searched the online databases Medline, Embase, the Cochrane library and the Cochrane Central Registry of Controlled Trials to select eligible control trials, including non-sleepy OSA patients and those patients treated by CPAP or either sham CPAP or no CPAP. Results: Seven eligible studies (1,541 patients) were included. The pooled estimates of the mean changes after CPAP treatment for the systolic blood pressure (SBP) and diastolic blood pressure (DBP) were −0.51 mmHg (95% CI, −3.39 to 2.38 mmHg; P=0.73) and −0.92 mmHg (95% CI, −1.39 to −0.46 mmHg; P